Different pathways of social protection reforms: An analysis of long-term institutional change in Kenya. (January 2021) - Bender, Katja; Rohregger, Barbara; Kinuthia, Bethuel; Ikua, Grace; Schüring, Esther; Adamba, Clement; Alatinga, Kennedy A.; Pouw, Nicky
Highlights: Theoretically, diversity in institutional change is explained by the interplay between preferences, institutions and uncertainty. In Kenya, cash transfer reforms show a pattern of cumulative incremental change, change in social health protection is obstructed. Contributing factors are stronger conflicting interests and institutional legacies within the area of social health insurance. Private information and the presence of focal points facilitated decision-making on cash transfers and fee waivers. Ambiguity and complexity sharpened the focus on cash transfers and exacerbated critical views on social health insurance. Abstract: The potential of social protection to contribute to inclusive growth has been increasingly recognized throughout the last two decades. Social protection reforms involve comprehensive processes of long-term institutional change. Dynamics differ not only across but also within countries across social protection pillars reflecting multiple institutional trajectories and equilibria ranging from rapid and comprehensive shifts over processes of gradual change to situations of blocked reforms or reform reversals. This paper seeks to understand why reforms aiming at extending social protection coverage to the poor might differ across different pillars of social protection within the same country. Being embedded within comparative institutional analysis the paper aims at providing a systematic framework for defining and explaining variations in reform dynamics highlighting the role of uncertainty. The framework is applied to the Kenyan case. The empirical methodology employs a process tracing approach including primary and secondary data covering the time period between 2001 and 2017. The case of Kenya is one example for multiple institutional trajectories within a country: Whereas cash transfer reforms follow a pattern of cumulative incremental change, social health protection reforms reflect patterns of non-cumulative change including blocked reforms and reform reversals. The results suggest that those differences are partly explained by differences in preferences among agents or the institutional legacies within each domain. In addition, behavioral responses to uncertainty matter: Stronger information asymmetries within the cash transfer and fee waiver reform domains opened space for discretionary decision-making. Interpretations of the concept of social protection and complexity of 'insurance' facilitated processes related to cash transfers whereas providing impediments to social health insurance. Lastly, the international and socio-economic context provided focal points facilitating coordination on targeted or vertical interventions such as cash transfers or fee waivers.